The Development of the ‘Mahaga’ Digital Authentic Assessment Instrument Based on the Project-Based STEM Approach to Enhance Elementary School Students’ Scientific Literacy - Rita Rahmaniati; Bulkani; Amelia Dwi Astuti; Citra Amalia (Postgraduate, University of Mataram, 2025)
This research developed a digital authentic assessment instrument based on a project-based STEM approach to enhance scientific literacy among elementary school students. This study aimed to create an instrument that is valid, practical, and effective. The research employed a Research and Development (R&D) approach, utilizing the ADDIE model. Data were collected through observation, interviews, and tests. The product’s practicality was assessed by media, evaluation, and material experts using closed questionnaires. Its effectiveness was measured via a pretest–posttest design conducted with small and large groups of students. A t-test and N-Gain analysis were used to evaluate the improvement of learning outcomes. The validation results were strong, with scores of 97% from the content expert, 94.5% from the assessment expert, and 95.5% from the media expert, indicating that the instrument was very valid. The practicality test also yielded a very practical score of 93% from student and teacher responses. For the effectiveness test, average scores increased from a pre-test of 58.2 to a post-test of 83.2, resulting in a medium N-Gain score of 0.59. This finding indicates that the use of the ‘MAHAGA’ digital authentic assessment is highly effective. These findings affirm ‘MAHAGA’ as a valid, practical, and effective instrument, offering a significant contribution to promoting scientific literacy in elementary education. This instrument offers a promising, innovative solution to advance science education at the elementary level, equip students with essential 21st-century skills, and support the development of a more adaptive, critical, and innovative generation.